1991
DOI: 10.2166/wqrj.1991.017
|View full text |Cite
|
Sign up to set email alerts
|

Photobacterium phosphoreum Toxicity Data Index

Abstract: This toxicity data index gives a compilation of some 1350 acute toxicity data of individual organic compounds for the luminescent marine bacterium Photobacterium phosphoreum, commonly known as Microtox™ test. The index contains 5-min, 15-min and 30-min toxicity data in both logarithmic (log (L/mmol) and non-logarithmic (mg/L) formats for approximately 1300 chemicals sorted by Chemical Abstracts Service (CAS) accession numbers. In addition to the toxicity data, this index reviews correlations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
139
1
8

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(160 citation statements)
references
References 0 publications
12
139
1
8
Order By: Relevance
“…Cationic herbicides are the least toxic to the bacteria, with EC 50 values which were even higher than 3000 µg/mL. The toxicity values are consistent with those obtained by other authors for carbaryl, carbofuran, diazinon and malathion, but paraquat seems less toxic than the results reported in the literature [Kaiser and Palabrica 1991;Somasundaran et al 1990). For most of the compounds tested in this study no data are available in the literature.…”
Section: *Test Solutions Prepared In Distilled Watersupporting
confidence: 88%
See 2 more Smart Citations
“…Cationic herbicides are the least toxic to the bacteria, with EC 50 values which were even higher than 3000 µg/mL. The toxicity values are consistent with those obtained by other authors for carbaryl, carbofuran, diazinon and malathion, but paraquat seems less toxic than the results reported in the literature [Kaiser and Palabrica 1991;Somasundaran et al 1990). For most of the compounds tested in this study no data are available in the literature.…”
Section: *Test Solutions Prepared In Distilled Watersupporting
confidence: 88%
“…According to the data obtained by different authors, the percentage of the solvent in the test solution should not be greater than 10%. Recommended percentages include 4% (Kwan and Dutka 1990), 5% (Kaiser and Palabrica 1991), 8% (Somasundaram et al 1990) and 10% (Kaiser and Ribo 1985).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary it has been shown that P. chrysogenum CLONA2 may find application in remediation of phenol and resorcinol contaminated saline water. Kaiser and Palabrica (1991) b Kahru et al (2000) …”
Section: Discussionmentioning
confidence: 99%
“…The tests based on naturallyoccurring marine bioluminescent bacteria as used in the Microtox test (Photobacterium phosphoreum or Photobacterium fischeri) or the ToxAlert test (Photobacterium fischeri or Vibrio fischeri 1 are in widespread use and they correlate inhibition of luminescence with toxicity [12,[76][77][78]. The tests are rapid, and reliable toxicity testing has been demonstrated [74,[79][80][81][82]: indeed, their use has resulted in the production of extensive databases on the toxicity of pure chemicals [83]. Futhermore, the Microtox assay has become an important part of German wastewater monitoring and assessment as outlined in both the federal Water Resources Management Act and the Wastewater Charges Act [84].…”
Section: Prokaryotic Sensorsmentioning
confidence: 99%